KONTEN DAKWAH: SEBAGAI SUMBER DUKUNGAN SPIRITUAL DAN MENTAL BAGI REMAJA DI DUNIA DIGITAL - Friska Rahmita Helmy; Grechia Perdina; Luluk Ludfia (STAI DI AL-HIKMAH, 2025)
The development of the digital world has significantly influenced teenagers' lives, particularly in spiritual and mental aspects. Generation Z youth live in a reality full of social pressure, self-expectation, and constant exposure to social media, leading to increased anxiety, stress, and loss of life purpose. In this context, Islamic preaching (dakwah) content on digital platforms such as YouTube, Instagram, and TikTok emerges as a vital alternative for offering both spiritual and mental support. This study employs a qualitative approach through literature review, examining academic sources from 2021 to 2025 and observing popular da’wah content relevant to adolescent issues. The findings reveal that digital da’wah serves as a form of non-clinical psychological therapy, directly reaching the emotions and spirituality of youth. Content delivered with a light tone, engaging visuals, and empathetic messaging effectively uplifts the spirit, calms the soul, and strengthens teenagers’ religious identity. The role of digital preachers extends beyond delivering religious teachings; they now act as spiritual counselors offering a safe space for teens to express their struggles. This study concludes that communicative and adaptive da’wah content is an effective form of spiritual intervention that supports adolescent mental health in the digital ageThis study shows that preaching through social media has a significant influence in shaping better Muslim personalities, both in terms of religious understanding, increasing worship, and changing behavior in accordance with Islamic values.